2011
DOI: 10.1080/09540121.2010.534436
|View full text |Cite
|
Sign up to set email alerts
|

Identifying barriers to HIV testing: personal and contextual factors associated with late HIV testing

Abstract: Late diagnosis of HIV is associated with increased morbidity, mortality, and health care costs. Despite the availability of HIV testing, persons continue to test late in the course of HIV infection. We used the HIV/AIDS case registry of San Francisco Department of Public Health to identify and recruit 41 persons who developed AIDS within 12 months of their HIV diagnosis to participate in a qualitative and quantitative interview regarding late diagnosis of HIV. Thirty-one of the participants were diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 23 publications
5
97
0
9
Order By: Relevance
“…Schwarcz et al reported that fear was the most frequently cited barrier to testing, as was being unaware of improved HIV treatment and risk for HIV. 13 Mass media campaigns, often included as part of the NHTD activities, can help address these barriers. Studies that evaluated the effects of mass media campaigns have shown significant Public Health Reports / September-October 2014 / Volume 129 improvements in information-seeking for HIV testing among African American women, 14 hotline calls about and receipt of HIV testing among adolescents, 15 and recall of HIV testing-related campaign material and HIV testing at partner clinics among Latinos.…”
Section: Discussionmentioning
confidence: 99%
“…Schwarcz et al reported that fear was the most frequently cited barrier to testing, as was being unaware of improved HIV treatment and risk for HIV. 13 Mass media campaigns, often included as part of the NHTD activities, can help address these barriers. Studies that evaluated the effects of mass media campaigns have shown significant Public Health Reports / September-October 2014 / Volume 129 improvements in information-seeking for HIV testing among African American women, 14 hotline calls about and receipt of HIV testing among adolescents, 15 and recall of HIV testing-related campaign material and HIV testing at partner clinics among Latinos.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-negative people get updated information on the primary prevention from the pre-and post-test counseling and the HIV-positive people get the opportunity of accessing to the psychosocial support, linkage to care and treatment [2]. On the other hand, delay in diagnosis of HIV infection is the most substantial obstacle to accelerate HIV treatment and prevention and increases morbidity, mortality, and health care costs [9]. The main objectives of the Joint United Nations Program on HIV/AIDS (UNAIDS) are to make voluntary HIV testing services 90% accessible to help 90% of people living with HIV to know their status, especially young people and those living in a high HIV prevalent settings [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Barriers to HIV testing fall within several well-described categories: individual level concerns including fear of results, internal and external stigma attached to testing, anxiety waiting for results, lack of recognition of risk status, and low HIV knowledge; provider level barriers such as lack of funding, limited awareness of testing guidelines, and discomfort; and system related barriers such as limited availability of rapid testing. [17][18][19][20] Although data regarding black non-U.S.-born individuals and HIV testing is limited, data from Europe indicate that black immigrants (primarily from sub-Saharan Africa) experience many of the same barriers as native born individuals, including fear of positive test results and its related personal and social consequences, lack of preventive health behavior, and denial of HIV risk. HIVrelated stigma, language barriers, and low HIV knowledge are also common.…”
mentioning
confidence: 99%